Reassessment of the sulfur and halogen emissions from the Millennium Eruption of Changbaishan (Paektu) volcano - Scaillet, Bruno; Oppenheimer, Clive (Journal of Volcanology and Geothermal Research, 2023)
International audience The 946 CE 'Millennium Eruption' of Changbaishan (aka Paektu) volcano ranks among the largest volcanic events of the Common Era. Its fallout represents a widespread preciselydated marker horizon yet little is known of its environmental impacts. Here, we revisit petrologic constraints on the pre-eruptive conditions of the dominant rhyolitic magma in order to estimate the eruption's volatile budget. We show that silicic reservoirs may lose more than half of their volatile complements prior to eruption and estimate that the Millennium Eruption emitted just 2-7 Tg of sulfur and 5-10 Tg of chlorine to the atmosphere, depending on the accepted eruption magnitude. These values are lower than previous petrologic estimates but consistent with ice core glaciochemistry and tree-ringbased climate reconstructions. We further suggest that any reawakening of Changbaishan / Paektu should be heralded by enhanced CO2 emissions if driven by basalt intrusion, or by H2-H2O-rich and halogen-poor gases if resulting from evolution of a silicic reservoir. Our findings emphasise the importance of robust assessments of pre-eruptive conditions, especially in respect of temperature, when applying petrologic arguments to evaluate outgassing from silicic volcanism.